Efficiencies of cobalt- and copper-based coatings applied by different deposition processes for applications in intermediate-temperature solid oxide fuel cells. (5th September 2022) - Tomas, M.; Asokan, V.; Puranen, J.; Svensson, J.-E.; Froitzheim, J.
Abstract: Solid Oxide Fuel Cells (SOFCs) are electrochemical conversion devices that produce electricity directly by oxidising a fuel. The interconnects between the individual cells need to be coated to limit Cr(VI) evaporation from the steel and to preserve electrical conductivity. Physical Vapour Deposition (PVD)-coated samples with Ce/Co, Ce/Cu, and Ce/MnCu, and Thermal Spray (TS)-coated Mn/Co, Cu and Mn/Cu and AISI 441 steel samples were exposed at 650 °C for up to 1000 h. The PVD Ce/Co and Ce/Cu coatings, as well as the TS Mn/Co coating, exhibited the formation of a thin protective Cr2 O3 scales underneath the coating. These samples also exhibited the lowest area-specific resistance (ASR) values. The remainder of the samples exhibited much higher mass gains and higher ASR values. Cr(VI) evaporation measurements showed that all the coatings behaved approximately the same despite the PVD coatings being only about one-tenth of the thickness of the TS coatings. Highlights: < 1 μm PVD coatings are as efficient as 10 μm thermal spray coatings at mitigating Cr evaporation. PVD Ce/Cu forms a conductive CuO top layer and conductive intermediate spinel. PVD Ce/Cu coating are equally good as PVD Ce/Co at 650 °C.